(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2022)
The explosion in cloud-native architectures and microservice-based distributed systems has brought about a level of complexity that cannot be effectively handled using traditional monitoring systems and manual incident handling strategies. This paper introduces a novel operational intelligence framework, based on the artificial intelligence, streaming, and auto-remediation facilities, to manage the high-scale cloud-native distributed systems. It comprises anomaly detection, predictive analysis, smart alerting, and auto-remediation. By using the data produced by containers, service mesh technologies, and cloud infrastructure, the system can deliver operational intelligence by employing machine learning, stream processing, and autonomous actions, and minimal human interaction is necessary. The proposed system architecture is vendor-neutral and extensible, which allows it to be compatible with popular observability products on the market. The paper addresses the system architecture, data flows, AI/ML model development, and deployment issues, putting a particular focus on how operational intelligence is applied in DevOps and SRE.